Development and Assessment of Alginate-Chitosan Microparticles loaded with Luteolin for Hydrophobic Drug Encapsulation - Ibrahim, Ibrahim Mohammed; Abubakar, Salisu; Yakubu, Ndatsu (International Journal of Scientific Research in Biological Sciences, 2024)
This research focus was stressed on creating Alginate-Chitosan (Alg-Cht)) loaded luteolin (LT) microparticles (MPs) able to function as carriers for the hydrophobic medications. LT is a water insoluble bioactive compound characterized by the presences of multiple unit of phenol belonging to the flavonoid family and offers a wide range of therapeutic benefits. MPs loaded with LT were created through the process of ionotropic gelation polyelectrolyte complexation using Cht, Alg, tripolyphosphate (TPP) and LT. Synthesized LT loaded Alg/Cht-MPs were evaluated for encapsulation efficiency, percentage yield, FTIRS, in vitro drug release, and antioxidant activity. Average particle size ranging from 2.1-4.0um, 4.1-6.0 and 8.1-10.0um, for Cht, Alg and Alg -Cht-MPs respectively. FTIRS analysis proved the drug interacted with the additives as they were a shift in the peaks the formulations displayed a notable impact on the encapsulation efficiency as well. (78.2, 68.8 and 87.4%) and percentage Yield (77.7, 92, and 87.4%) for Cht, Alg and Alg/Cht-MPs respectively. The results for in vitro release study revealed improved drug release as formulations (Cht, Alg, and Alg/Cht-MPs) showed a maximum drug release of 67.4, 62.4, and 78.9% respectively, while pure LT showed only 20.1% within 24hrs. The release data revealed significant variation (p < 0.005) in the release pattern. The antioxidant activity for the formulations showed greater activity compared to pure LT at 0.5mg/ml concentration, the radical scavenging effect of Cht, Alg, and Alg/Cht-MPs was 80.8, 78.6 and 89.4% respectively compared to pure LT 76.3±0.7%. From this results imply that the enhanced drug release from MPs was achieved due to the enhanced solubility of LT in the presence of the polymers. Formulation with Alginate/Chitosan microparticles could be a promising carrier for the encapsulation of the hydrophobic bioactive compound combining safety profile and enhanced drug protective activity.